2006
DOI: 10.1897/05-614r.1
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of cause‐effect relationships between polychlorinated biphenyl concentrations and sediment toxicity to benthic invertebrates

Abstract: Cause-effect sediment-quality benchmarks for the protection of benthic invertebrates are needed for polychlorinated biphenyls (PCBs) to support predictive risk assessments and retrospective evaluations of the causes of observed sediment toxicity. An in-depth evaluation of PCB aquatic toxicity and organic carbon partitioning was conducted to predict sediment effect concentrations using the equilibrium partitioning (EqP) approach. This evaluation was limited to invertebrate toxicity data, because PCBs may exert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(53 citation statements)
references
References 69 publications
3
50
0
Order By: Relevance
“…Furthermore, it is far below the mechanistically based benchmarks reported elsewhere (e.g., Fuchsman et al 2006), even though the latter are expressed as Aroclors. The Rhone SQG proposed is also comparable to the total PCBs fca-SQT ranging from 1 to 60 ng g −1 (dw) determined by Bhavsar et al (2010) for several Great Lakes locations and four species.…”
Section: Sqg Calculationmentioning
confidence: 61%
“…Furthermore, it is far below the mechanistically based benchmarks reported elsewhere (e.g., Fuchsman et al 2006), even though the latter are expressed as Aroclors. The Rhone SQG proposed is also comparable to the total PCBs fca-SQT ranging from 1 to 60 ng g −1 (dw) determined by Bhavsar et al (2010) for several Great Lakes locations and four species.…”
Section: Sqg Calculationmentioning
confidence: 61%
“…Because our chronic toxicity PCB concentrations are based exclusively on Aroclor mixtures (Tables and ), selecting an Aroclor‐specific K OW value was our principal approach for EqP modeling in the present investigation. The homolog approach used by Fuchsman et al is found in the Discussion section, as is a congener approach; however, neither matches with the Aroclor‐based injury data from Tables and . The handbook published by Mackay et al may be one of the most widely cited and respected sources for physical–chemical properties of organic chemicals.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we used the theoretical EqP approach to generate a continuum of benthic injury dose responses for sediments contaminated with PCBs. We compare our approach with threshold values reported by Fuchsman et al . We discuss important uncertainties associated with the use and application of the benthic injury dose–response curve for PCB‐contaminated sediments.…”
Section: Introductionmentioning
confidence: 98%
“…Polychlorinated biphenyls are persistent, hydrophobic, and bioaccumulative contaminants, which are widely distributed and listed as endocrine disrupters and probable carcinogens to humans [33]. Even when aqueous PCB concentrations in overlying water are below the acutely toxic level (%7 ppm [1]), chronic effects have been observed on organism growth, reproduction, survival, and life span as well as teratogenic effects in wildlife [34][35][36].…”
Section: Sediment Characteristicsmentioning
confidence: 99%
“…Contaminants in sediment that cause chronic toxicity can simplify community structures by reducing the abundance of sensitive species and increasing the abundance of tolerant species [1][2][3]. If changes in the benthic community can be attributed to major pollutants like PCBs, then sediment remediation strategies could more directly be evaluated based on their capability to mitigate exposure and risk and to allow for recovery.…”
Section: Introductionmentioning
confidence: 99%